2021
DOI: 10.1021/acschemneuro.0c00791
|View full text |Cite
|
Sign up to set email alerts
|

Radiochemical Synthesis and Evaluation in Non-Human Primates of 3-[11C]methoxy-4-aminopyridine: A Novel PET Tracer for Imaging Potassium Channels in the CNS

Abstract: Demyelination, the loss of the protecting sheath of neurons, contributes to disability in many neurological diseases. In order to fully understand its role in different diseases and to monitor treatments aiming at reversing this process, it would be valuable to have PET radiotracers that can detect and quantify molecular changes involved in demyelination such as the uncovering and upregulation of the axonal potassium channels K v 1.1 and K v 1.2. Carbon-11 labeled radiotracers present the advantage of allowing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(45 citation statements)
references
References 30 publications
4
41
0
Order By: Relevance
“…A recent report of 4-AP treatment in patients with KCNA2-encephalopathy has interesting mechanistic implications; 4-AP reduced seizures in patients with gain-of-function variants of the Kv1.2 subunit and antagonized the electrophysiological defects in vitro in transfected neurons that expressed variant Kv1.2 channels [ 37 ]. In addition, methods to evaluate 4-AP target engagement and potential mechanism(s) of action in the brain may be facilitated by development of a 4-AP radioligand for neuroimaging, which has detected cortical pathology from brain injury in nonhuman primate testing and has advanced to a clinical trial [ 9 , 36 ]. The need for treatments for acute TBI and the promising results of our present study suggest the importance of repurposing 4-AP for TBI as a new clinical indication.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report of 4-AP treatment in patients with KCNA2-encephalopathy has interesting mechanistic implications; 4-AP reduced seizures in patients with gain-of-function variants of the Kv1.2 subunit and antagonized the electrophysiological defects in vitro in transfected neurons that expressed variant Kv1.2 channels [ 37 ]. In addition, methods to evaluate 4-AP target engagement and potential mechanism(s) of action in the brain may be facilitated by development of a 4-AP radioligand for neuroimaging, which has detected cortical pathology from brain injury in nonhuman primate testing and has advanced to a clinical trial [ 9 , 36 ]. The need for treatments for acute TBI and the promising results of our present study suggest the importance of repurposing 4-AP for TBI as a new clinical indication.…”
Section: Discussionmentioning
confidence: 99%
“…Docking experiments were performed on the IFD (induced fit docking) program (28) from the extra precision (XP) mode calculations. The prepared protein and ligand were put together to initiate the docking via flexible docking mode.…”
Section: Docking Methodologymentioning
confidence: 99%
“…Previously developed 68 Ga-labeled homodimeric chalcone-DTPA complex displayed promising results in preliminary PET imaging studies (26). Increased specificity due to the presence of N,N-dimethylamino groups on the chalcone moiety and thermodynamically stable dimeric structure make this molecule a potential candidate for utilization as an imaging probe (27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…Prior comparison between the previously developed tracers [ 11 C]3MeO4AP and [ 18 F]3F4AP using the Guo method 28 had shown a very good correlation between the two tracers (r = 0.93), suggesting a common target 16 . This comparison also indicated that and when compared with [ 11 C]3MeO4AP the intercept was greater than 0 (y = 0.67, p = 0.31).…”
Section: Quantitative Comparison Of [ 11 C]3me4ap With [ 18 F]3f4ap A...mentioning
confidence: 99%
“…Furthermore, [ 18 F]3F4AP was very sensitive to a focal brain injury in a monkey 14 . More recently, due to the advantages of having short-lived radiotracers, such as allowing multiple scans on the same subject on the same day, we explored 3-[ 11 C]trifluoromethyl-4-aminopyridine ([ 11 C]3CF34AP) 15 and 3-[ 11 C]methoxy-4-aminopyridine ([ 11 C]3MeO4AP) 16 as viable 11 C-labeled alternatives. Compared to [ 18 F]3F4AP, [ 11 C]3CF34AP showed higher brain penetration and faster washout with lower heterogeneity across brain regions, which is consistent with its higher lipophilicity and lower binding affinity as was measured in vitro 17 .…”
Section: Introductionmentioning
confidence: 99%